Effects of somatostatin on renal function in cirrohotic patients with ascites - Yusuf UZUN; Abdulkadir DÖKMECİ and Hasan ÖZKAN and Hakan BOZKAYA and Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2019)
-